Study on the mechanical properties of desert sand concrete under dry-wet cycles with sulfate erosion - Xu, Wenjing; Liu, Haifeng; Doh, Shu Ing (Elsevier Ltd., 2025)
To evaluate the potential application of desert sand concrete (DSC) in the construction industry, the evolution of its properties in the conjoint impact of sulfate corrosion and dry-wet (D-W) cycles was investigated. In this study, a range of variables were taken into account, including desert sand replacement rate (DSRR, 0,40,60%), D-W cycles (0, 30, 60, 90, 120 and 150 cycles) and mass fraction of sodium sulfate solution (3, 5 and 7%). The performance deterioration of DSC such as ultrasonic parameters, dynamic elastic modulus and damage parameters were analyzed under sulfate environment. Uniaxial compression tests ascertained the peak stress, peak strain and the compressive stress-strain curve of DSC under a range of sulfate D-W cycles. Microscopic testing techniques such as scanning electron microscopy (SEM) and X-ray diffraction (XRD) were utilized to examine the microstructure morphology and phase composition of DSC. The experimental findings demonstrated that the ability of DSC to resist corrosion characteristics could be effectively improved under sulfate attack and D-W cycles when desert sand was added at 40%. The peak stress of DSC was improved first and then diminished with the progression of D-W cycles, attaining the maximum value at 60 D-W cycles, while peak strain gradually decreased and then increased. SEM and XRD test results revealed that sulfate crystals and continuing formation of expansive materials like gypsum (CaSO4⋅2 H2O) and ettringite (AFt) were the principal elements causing the degradation of DSC as the D-W cycles increased.